2007
DOI: 10.1021/np0703500
|View full text |Cite
|
Sign up to set email alerts
|

Triterpene Glycosides from the Roots of Astragalus flavescens

Abstract: Six new triterpene saponins, 3-O-alpha-L-rhamnopyranosyl-(1-->2)-beta-D-xylopyranosyl-(1-->2)-beta-D-glucuronopyranosyl-21-epi-kudzusapogenol A (1), 3-O-alpha-L-rhamnopyranosyl-(1-->2)-beta-D-glucopyranosyl-(1-->2)-beta-D-glucuronopyranosyl-21-epi-kudzusapogenol A (2), 3-O-alpha-L-rhamnopyranosyl-(1-->2)-beta-D-xylopyranosyl-(1-->2)-beta-D-glucuronopyranosyl-22-O-beta-D-glucopyranosyl-21-epi-kudzusapogenol A (3), 3-O-alpha-L-rhamnopyranosyl-(1-->2)-beta-D-glucopyranosyl-(1-->2)-beta-D-glucuronopyranosyl-22-O-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 11 publications
1
25
0
1
Order By: Relevance
“…Unambiguous assignments of proton and carbon resonances in the NMR spectra were based on extensive analysis of HSQC, 1 H-1 H COSY and TOC-SY spectra of 8. The two anomeric carbon signals at d C 103.4 and 102.6 in combination with the chemical shifts and coupling patterns of the two anomeric protons [4.18 (d, J = 6.7 Hz) and 4.63 (d, J = 6.9 Hz)] and other characteristic NMR resonances, suggested that the two sugar moieties were b-xylopyranosyl and bglucopyranosyl, respectively (Agrawal, 1992;Avunduk et al, 2008). The sugar sequence and their linkage sites were derived from the 13 C-1 H long-range correlation signals at H-1 glc (d H 4.63)/C-5 (d C 152.2); H-1 xyl (d H 4.18)/C-6 glc (d C 68.3), and H-6 glc (d H 3.52, 3.94)/C-1 xyl (d C 103.4) in its HMBC spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…Unambiguous assignments of proton and carbon resonances in the NMR spectra were based on extensive analysis of HSQC, 1 H-1 H COSY and TOC-SY spectra of 8. The two anomeric carbon signals at d C 103.4 and 102.6 in combination with the chemical shifts and coupling patterns of the two anomeric protons [4.18 (d, J = 6.7 Hz) and 4.63 (d, J = 6.9 Hz)] and other characteristic NMR resonances, suggested that the two sugar moieties were b-xylopyranosyl and bglucopyranosyl, respectively (Agrawal, 1992;Avunduk et al, 2008). The sugar sequence and their linkage sites were derived from the 13 C-1 H long-range correlation signals at H-1 glc (d H 4.63)/C-5 (d C 152.2); H-1 xyl (d H 4.18)/C-6 glc (d C 68.3), and H-6 glc (d H 3.52, 3.94)/C-1 xyl (d C 103.4) in its HMBC spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis and determination of biological activities of various compounds are very important strategies owing to their large‐scale usefulness in industrial and medicinal areas 10,28,29. In this regard, synthetic β‐aminoketones, which is a Mannich base derivative formed in the reaction of an amine, formaldehyde (or an aldehyde), and a carbon acid, have a great potential to be candidates for industrial and medicinal applications.…”
Section: Discussionmentioning
confidence: 99%
“…In the 1 H NMR spectra of the compounds, the relatively large 3 J H-1,H-2 values of the glucose, xylose, and galactose (between 7.0 and 8.0 Hz) moieties indicated a b anomeric proton. The broad singlet of the anomeric proton of the rhamnose unit indicated an a-orientation (Avunduk et al, 2008).…”
Section: Phytochemical Investigationmentioning
confidence: 99%